Reinforcing Stage Two in the EMU Process. - Niels Thygesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1994)
The paper initially discusses monetary policies in the context of the wide margins introduced on 1 August 1993. The new President of the European Monetary Institute (EMI) has suggested that a number of stringent non-monetary conditions must be met before there can be a return to narrow margins. While this list may be too comprehensive, the paper argues that there are also some monetary prerequisites which will be difficult to meet: at a minimum some mixture of less conditionality in interventions on behalf of creditor central banks and strong incentives for debtor central banks to raise interest rates to defend their currencies. The paper finds a continuation of wide margins for most of the transition realistic. Such a scenario might have certain advantages in relation to the transition to monetary union, provided participants continue to value exchange rate stability highly. In the second part the specific role of the EMI is reviewed. To the extent that the EMI President, the Director-General and other senior members of the staff succeed in taking charge of the work in the Council, The Alternates' Committee and the various writing groups monetary coordination and the preparations for full monetary union should be enhanced. The latter would also be helped if the EMI were to be given some operational functions beyond the passive holding and managing of internaitonal reserves specifically mentioned in the Treaty. An operational role also in domestic money market operations and in clearing in the ecu market appears desirable.
Keywords: 330